Internal audit in banking, based risk assessment - Espinoza Huere, Florencio (2017)
The present research confirms the efficiency and effectiveness of the internal audit based on risk assessment, as a scientific discipline provides, evaluates, monitors and reduces the risks that arise in banking, using methodologies, policies and technical standards approach  risks, to ensure quality improvements in the internal audit process, and for this purpose we used the non-experimental research design.